Legal Assistance (Social Advocacy) on The Civil Rights of Indonesian Migrant Workers in The Sumber Gede Community - Nurhidayati; Nugraha, Satriya; Pitriani; Zulfikar, Ahmad Arif; Nuriasari, Selvia (Research and Social Study Institute, 2022)
The phenomenon of migrant workers in Indonesia is one of the issues that often cause public unrest. Migrant workers are considered foreign exchange heroes for the country. However, often the problems that afflict these migrant workers are unknown and even untouched while still working or after working as a migrant workers. The purpose of the activity is to provide legal assistance (social advocacy) to the village government and migrant workers to ensure the fulfillment of the rights of migrant workers and increase the capacity of both knowledge and legal information for migrant workers and former migrant workers once a month, provide legal protection information and improve the competence of PMI families and increase the ability and competence of PMI candidates in Sumber Gede Village community every three months. The method used is the Participatory Rural Appraisal (PRA) method. It is carried out in Sumber Gede Village, East Lampung Regency, through the stages of problem identification, activity planning, coordination with partners, implementation of activities, and supervision and evaluation. The exercises are strengthening legal literacy through the socialization of the law. No. 18 of 2017 on the protection of Indonesian migrants and Sumber Gede Village Regulation No. 4 of 2021 on the protection of Indonesian migrants, Gender-responsive Case Management Training and Paralegal Training in case handling for women migrant workers. The result of this activity is to increase competence and knowledge for migrant workers, former migrant workers and migrant workers' families both in terms of regulatory knowledge, legal assistance, and improving entrepreneurial skills.